Glucagon-like peptide-1 (GLP-1) mediates cardioprotection by remote ischaemic conditioning. Issue 3 (4th October 2016) - Basalay, Marina V.; Mastitskaya, Svetlana; Mrochek, Aleksander; Ackland, Gareth L.; del Arroyo, Ana Gutierrez; Sanchez, Jenifer; Sjoquist, Per-Ove; Pernow, John; Gourine, Alexander V.; Gourine, Andrey
Abstract : Aims: Although the nature of the humoral factor which mediates cardioprotection established by remote ischaemic conditioning (RIc) remains unknown, parasympathetic (vagal) mechanisms appear to play a critical role. As the production and release of many gut hormones is modulated by the vagus nerve, here we tested the hypothesis that RIc cardioprotection is mediated by the actions of glucagon-like peptide-1 (GLP-1). Methods and results: A rat model of myocardial infarction (coronary artery occlusion followed by reperfusion) was used. Remote ischaemic pre- (RIPre) or perconditioning (RIPer) was induced by 15 min occlusion of femoral arteries applied prior to or during the myocardial ischaemia. The degree of RIPre and RIPer cardioprotection was determined in conditions of cervical or subdiaphragmatic vagotomy, or following blockade of GLP-1 receptors (GLP-1R) using specific antagonist Exendin(9–39). Phosphorylation of PI3K/AKT and STAT3 was assessed. RIPre and RIPer reduced infarct size by ∼50%. In conditions of bilateral cervical or subdiaphragmatic vagotomy RIPer failed to establish cardioprotection. GLP-1R blockade abolished cardioprotection induced by either RIPre or RIPer. Exendin(9–39) also prevented RIPre-induced AKT phosphorylation. Cardioprotection induced by GLP-1R agonist Exendin-4 was preserved following cervical vagotomy, but was abolished in conditions of M3 muscarinic receptor blockade. Conclusions: These data strongly suggest that GLP-1 functions as a humoral factor of remote ischaemic conditioning cardioprotection. This phenomenon requires intact vagal innervation of the visceral organs and recruitment of GLP-1R-mediated signalling. Cardioprotection induced by GLP-1R activation is mediated by a mechanism involving M3 muscarinic receptors.